Pengaruh Label Halal, Gaya Hidup, Harga Produk Dan Keamanan Terhadap Keputusan Pembelian Terhadap Keputusan Pembelian Wardah (Studi Kasus Mahasiswa FEB UNISMA Tahun Angkatan 2019) - Umatuz Sukmawati; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The public's absorption of high cosmetic products and the increasing number of beauty industry companies in Indonesia are one of the reasons why this research was carried out. Specifically in this study, the author will discuss Wardah's beauty products, where Wardah products offer halal-certified cosmetics. This study's major goal is to determine and evaluate how the halal label, lifestyle, product pricing, and safety affect Wardah purchase decisions. In this study, the object chosen was a student of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019 as a respondent. By using causal or explanatory research methods where this method determines the cause and effect between the two events that occur. The results of the study show that: 1) The presence of the Halal label has no discernible influence on purchase choices. 2) Lifestyle significantly influences buying decisions in a favorable way. 3) Product costs have no appreciable influence on consumers' purchasing choices. 4) Security significantly influences a buyer's decision to buy. Keywords: Purchase Decicion, Halal Label, Lifestyle, Product Price, Security.